Assessment of a telemedicine innovation in cardiology. (17th December 2009) - Masella, Cristina; Zanaboni, Paolo
Recently, in all of the national health systems, the need to keep health costs under control and to assure high-quality standards shifted the attention from hospitals to primary cares, territorial structures and patient homes. In this context, telemedicine represents a strong feature to satisfy the need for new clinical management approaches allowing patients with chronic diseases to effectively receive care in a home setting. The application of new telemedicine services always requires an assessment that considers, on the one hand, the responsibility of healthcare manufacturers in supplying high-quality and user-friendly technologies, and, on the other hand, the responsibility of healthcare organisations in providing cost-effective telemedicine services. In this context, this work aims at assessing the adoption of a remote monitoring service for follow-up examinations of chronic heart failure patients implanted with biventricular implantable cardioverter defibrillator. The assessment is conducted through a complete framework that explores the clinical utility, the technical feasibility, the economic implications and the customer satisfaction.